Empowering Posyandu Cadres through Assistance in Making Moringa Pudding as an Alternative PMT for Toddlers in Kurung Village, Kejayan, Pasuruan - Miftahillah Miftahillah; Mokh. Fatkhur Rokhzi; Khusnul Khotimah (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2026)
Toddler nutrition problems in rural areas require affordable, practical, and community-sustained interventions. Kurung Village, Kejayan District, Pasuruan Regency has abundant moringa (Moringa oleifera) resources; however, their utilization for supplementary feeding remains limited because Posyandu cadres have not yet acquired adequate food-processing skills. This community service program aimed to empower Posyandu cadres through nutrition education and mentoring in the preparation of moringa pudding as a local-food-based supplementary feeding alternative. The program applied a participatory approach consisting of preparation and administrative approval, nutrition socialization, hands-on training, independent mentoring, monitoring, and sustainability advocacy. The results showed an increase in cadres' knowledge from an average pre-test score of 52.4 to 88.6 in the post-test, representing a gain of 36.2 points. The moringa pudding developed through the program had a soft texture, attractive color, and reduced herbal odor. Acceptability evaluation showed that 85% of the target toddlers consumed the pudding completely, 10% consumed most of it, and 5% refused it because they were ill or experiencing acute picky eating. The program also secured the commitment of the Kurung Village Government to integrate the procurement of moringa-based supplementary feeding ingredients into the health allocation of the Village Fund. This mentoring program indicates that practice-based cadre capacity building can strengthen local competence and support the sustainability of community-based nutrition interventions.